Faktor Determinan Pengungkapan Corporate Social Responsibility dengan Kinerja Keuangan sebagai Variabel Mediasi - Safitri, Iis; Rahman, Taufikur (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
Abstract This study aims to determine the effect of green accounting, public share ownership, and environmental performance on disclosure of corporate social responsibility with financial performance as an intervening variable at JII 70 Company for the 2018-2020 period. This research is a type of secondary data quantitative research whose data is in the form of panel data with purposive sampling technique. The sample used was 24 companies registered in JII 70 for the 2018-2020 period. The data collection method is done by accessing the financial reports and annual reports which can be accessed through the website www.idx.co.id. The data was processed using the analytical tool Eviews10. The descriptive test, stationarity test, regression test, classical assumption test, path analysis test (path analysis), and Sobel test are the analytical methods employed. The findings revealed that the environmental performance variable, as well as financial performance, had a negative and significant impact on CSR disclosure. The disclosure of Corporate Social Responsibility is unaffected by the green accounting variable of public share ownership. Financial performance variables cannot mediate the influence of Green Accounting, Public Share Ownership, and Environmental Performance on Corporate Social Responsibility Disclosures after doing path analysis and Sobel tests. Key Words: Green Accounting, Public Share Ownership, Environmental Performance and Financial Performance